Maya blue: unlocking the mysteries of an ancient pigment - Arnold, Dean E., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2024)
Discusses Professor Dean Arnold's scientific journey to further the understanding of the unusual pigment known as Maya Blue.--Provided by publisher.
Why Is Maya blue unique? -- Palygorskite and Maya Indigenous knowledge -- Sources of palygorskite: Maya cultural heritage -- Other sources of palygorskite -- Maya blue and indigo -- Identifying ancient sources of palygorskite used in Maya blue -- How was Maya Blue made? -- Did the Maya use other methods to create Maya blue? -- How did Maya blue diffuse through Mesoamerica?
Keywords: Maya blue -- History; Mayas -- Material culture -- Mexico -- Yucatán (State); Mayas -- Mexico -- Yucatán (State) -- Antiquities; Palygorskite -- Mexico -- Yucatán (State); Indigo -- Mexico -- Yucatán (State); Pigments